2023
DOI: 10.1039/d3ma00794d
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of hierarchical porous structure for stretchable superhydrophobic films by delicately controlling the surface energy

Shuhan Hou,
Insub Noh,
Meng Yue
et al.

Abstract: Herein, thermoplastic polyurethane (TPU) was not only used as decorator for modified silica (m-SiO2), but also used as flexible polymer substrate combining with PAI for improving the robustness of stretchable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…This phenomenon led to the physical encapsulation of the microparticles. Recently, Hou et al reported a durable, stretchable superhydrophobic surface with the help of self-assembled hierarchical porous structures [60]. An alloy of poly(amide-imide) (PAI) and thermoplastic polyurethane (TPU) with a tensile strength of above 40 MPa and an elongation at a break approaching 300% was employed as an elastic substrate.…”
Section: Covering Elastomers With a Layer Of Rough And Low Surface En...mentioning
confidence: 99%
“…This phenomenon led to the physical encapsulation of the microparticles. Recently, Hou et al reported a durable, stretchable superhydrophobic surface with the help of self-assembled hierarchical porous structures [60]. An alloy of poly(amide-imide) (PAI) and thermoplastic polyurethane (TPU) with a tensile strength of above 40 MPa and an elongation at a break approaching 300% was employed as an elastic substrate.…”
Section: Covering Elastomers With a Layer Of Rough And Low Surface En...mentioning
confidence: 99%